2013
DOI: 10.1007/s12550-013-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Fusarium Mycotoxin Fumonisin B1 and B2 in Animal Feeds in Korea

Abstract: The objective of this study was to monitor the occurrence and levels of fumonisin B1 (FB1) and fumonisin B2 (FB2) in animal feeds distributed in South Korea in 2011. The contamination levels of FB1 and FB2 were investigated in 150 samples of compound feeds and in 40 samples of feed ingredients. The contamination rate of feed ingredients with FB1 and FB2 was 50 and 40%, respectively. FB2 was only found in samples contaminated with FB1. Of the compound feeds, 85% were contaminated by FB1 and 47% were contaminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
2
6
1
1
Order By: Relevance
“…Notably, the DDGS, corn bran, corn germ meal, corn gluten meal, wheat, and rice bran samples were 100% co-contaminated with AFB 1 , ZEN and DON in all the tested samples, and more than 96.4% complete pig feeds were co-contaminated with these three mycotoxins. These outcomes were consistent with previous investigations that revealed that mycotoxin co-occurrence is an extremely common problem in feed industry world widely [ 23 , 25 , 31 , 32 , 33 , 34 , 35 ]. Because current safety regulations do not consider the toxic potential of co-occurring mycotoxins, the combined effects on animal and human health are probably under estimated; these combined toxic effects need to be investigated further and should be taken into consideration when new regulatory limits are set in the future.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, the DDGS, corn bran, corn germ meal, corn gluten meal, wheat, and rice bran samples were 100% co-contaminated with AFB 1 , ZEN and DON in all the tested samples, and more than 96.4% complete pig feeds were co-contaminated with these three mycotoxins. These outcomes were consistent with previous investigations that revealed that mycotoxin co-occurrence is an extremely common problem in feed industry world widely [ 23 , 25 , 31 , 32 , 33 , 34 , 35 ]. Because current safety regulations do not consider the toxic potential of co-occurring mycotoxins, the combined effects on animal and human health are probably under estimated; these combined toxic effects need to be investigated further and should be taken into consideration when new regulatory limits are set in the future.…”
Section: Discussionsupporting
confidence: 93%
“…The breeding pregnancy feed was contaminated with the highest levels of FBs, and the mean level of contamination was 1.108 mg/kg. These FBs levels were lower than the levels previously reported by our research group in animal feeds distributed in South Korea in 2011 [16] and they were all lower than those mentioned in the commission regulation of the European Community. However, Martins et al (2011) reported that 8.7% of swine feed samples in Portugal were contaminated with FBs in 2010, which is significantly lower than the percentage observed in this study [17].…”
Section: Resultscontrasting
confidence: 75%
“…Several research articles reported that the levels of mycotoxins in compound feeds were lower than those observations in feed ingredients [13,14] mainly due to the dilution of mycotoxins by cleaning and mixing steps during processing. However, in our previous reports related to contamination of Fusarium mycotoxin (FB 1 , FB 2 , and beauvericin) in animal feeds in Korea, we also found higher contamination levels in compound feeds than those levels in feed ingredient [15,16] as shown in the present study. This tendency can be explained by following two points of view.…”
Section: Resultssupporting
confidence: 61%
“…A study in Brazil was conducted (during 2007–2010) to detect fumonisins in corn-based food products and reported that FB1 and FB2 were present in 82% and 51% of the examined products, respectively [116]. Contaminations by FB1 and FB2 observed in poultry broiler and feed fatting calves in South Korea [117]. Abdallah et al [118] found the co-occurrence of FB2 and ochratoxin A and B in the date palm.…”
Section: Effects On Agriculture and Foodmentioning
confidence: 99%